Determination of Total Phenolic Contents and Antioxidant Activities of Different Extracts Obtained from Morus alba L. (White Mulberry) Leaf - Nurcan Kılıç Baygutalp; Sedanur Kasimoğullari; Lale Duysak (Pharmata)
Objective: The plant known as white mulberry, or Morus alba L., has several uses and is employed in traditional medicine in many different cultures. The objectives of this study are to determine the total phenolic component and antioxidant levels of the methanol and ethanol extracts of leaves of Morus alba L. (White mulberry). Methods: Using the techniques of DPPH (1,1-diphenyl-2-picrylhydrazyl), FRAP (Iron ion that decreases antioxidant power), and CUPRAC (Copper ion that reduces antioxidant capacity), the antioxidant activities of methanol and ethanol extracts of Morus alba L. leaves were examined. Additionally, the Folin-Ciocalteu Reagent (FCR) technique was used to evaluate the total phenolic content of the ethanol and methanol extracts. To determine the antioxidant capacity of extracts, reference samples were used to prepare various concentrations ranging from 1 to 100 μg/mL. The extract's equivalent antioxidant capacity was determined using sample concentrations of 125, 250, and 500 μg/mL. Results: The methanol and ethanol extracts of the leaves of the Morus alba L. (White mulberry) plant were found to have the greatest level of phenolic compounds at the 500 μg/mL concentration of extracts. It was determined that the Trolox Eq value of methanol extract was higher in the DPPH, FRAP and FCR methods, and the Trolox Eq value of the ethanol extract was higher in the CUPRAC method. Conclusion: The possible folk medicinal application of Morus alba L. is supported by this study. Determining the precise mechanisms of action of the extracts, the best extraction technique, the ideal dosage, and any possible adverse effects is needed.